Serum Indicators Reflecting Gastric Function May Also Correlate with Other Extragastric Diseases - Yuehua Gong; Wei Wang; Yi Li; Yuan Yuan (Gastroenterology Research and Practice)
Aim. Serological indicators of organ function can reveal intrinsic links between different organs. The present study aimed to determine the correlations of serum indicators for gastric and extragastric function. Methods. A total of 823 individuals were enrolled. Data on indicators reflecting blood lipids, blood glucose, indexes of stomach, kidney, liver, and thyroid function, and H. pylori IgG antibody level were collected. Results. As creatine (Cr) levels increased, PGI (pepsinogen I), PGII concentrations, and PGI/II ratio increased monotonically from 79.7 to 105.15 µg/L, 6.5 to 8.4 µg/L, and 11.97 to 12.27, respectively (P<0.05). As thyroid peroxidase antibody (TPOAb) levels increased, PGI level decreased from 100.85 to 84 µg/L (P<0.05) and as thyroid stimulating hormone (TSH) increased, PGI/II ratio increased monotonically from 11.54 to 12.68 (P<0.05). As triglyceride (TG) levels increased, gastrin 17 (G17) concentrations increased monotonically from 1.73 to 2.7 pmol/L (P<0.05). As serum glucose and glycated hemoglobin (HbA1C) increased, PGI/II concentrations increased monotonically from 11.98 to 12.67 and 9.7 to 13.54 (P<0.05), respectively. Conclusions. Serum PG and G17 levels were associated with blood glucose and lipids, kidney function, and thyroid function but not with liver function. Serum indicators reflecting gastric function may correlate not only with primary diseases, but also with other extragastric diseases.